Analysis of the Link between CO2 Outflows, Energy Utilization, and Economic Development in a Developing Country: Evidence from Republic of Congo - Pea-Assounga, Jean Baptiste Bernard; Yao, Hongxing; Peprah, Philip Agyei; Ali, Shaibu (International Journal of Sustainable Energy and Environmental Research, 2020)
Developing countries play a number one role in international green-economic development as key holders of green products, and services. Nonetheless, these countries are not sufficiently concerned within the debates on expansion policies, due to their crucial implication in worldwide feasible development. This research aims to analyze the relationship between CO2 outflows, energy utilization, and economic development in the Republic of Congo as well as the presence of a causative link between the factors by applying the Vector Autoregressive model, including as additional proxies’ variables gross-fixed-capital-formation, and rural population. The data cover the period 1985-2018 using cointegration and causality techniques as a methodological approach. The Granger causality test outcomes of cointegrated variables showed that there is one-way Granger causality running from real GDP to Energy utilization, and running from dioxide outflows to real income as well as two–way causative link between Energy utilization and CO2 outflows in Congo. The results also display a bidirectional causal link between the rural population and Energy utilization. Overall evidence confirms that the practice of energy conservancy approach may lead to a significant and negative effect on economic development.